The Origins of Food Supplied to an Australian Public Hospital - Faulkner, Kathy; Gilbertson, Heather; Porter, Judi; Collins, Jorja (Frontiers in Nutrition, 2022)
Local food procurement by public institutions such as hospitals offers multiple benefits including stimulating the local economy, creating jobs, and building resilience within the food supply. Yet no published study has attempted to quantify the local food purchase by hospitals. This baseline is needed to identify gaps, set targets, and monitor change. The objective of this study was to investigate the origin of food supplied to a metro tertiary public hospital and to describe the proportion of food budget spent on items with ingredient grown in Australia and ‘locally’ within the state of Victoria. Food procurement data were collected and analyzed during October 2020-April 2021. All items purchased by the cook fresh kitchen supplying meals to inpatients and an onsite childcare during an 8-day menu cycle period were audited. Following an inspection of food packaging labels to determine country of origin, data on the proportion of Victorian content were collected from manufacturers and suppliers of foods containing Australian ingredient. Almost 80% of the food budget (AU $17,748 and 200 items) was spent on items containing significant (at least 75%) Australian content, while 11% was spent on entirely imported foods. The specific geographic origins of 55% of the budget spent on ‘Australian’ food remain unknown as information from manufacturers and suppliers was not available. Where data were available, 3% of food budget was attributed to entirely Victorian grown foods, including fresh fruit, vegetables, and poultry. A considerable proportion of Australian grown foods are purchased by this hospital, but it is largely unknown whether these are local, from the state of Victoria, or not. Tracing and sharing of food origin data, a clear definition for ‘local’ food, and an understanding of Victorian food growing industries are needed to progress the ‘local food to hospital’ agenda.